Nutritional Profile and Potent Antioxidant Activity of Saraba Keke: A Traditional Manadonese Functional Beverage - Kusmiyati Kusmiyati; Gusti Ayu Tirtawati; Maria Terok; Pande Putu Purwaningsih (Media Publikasi Cendekia Indonesia, 2026)
Saraba Keke is a traditional Manadonese beverage, but its nutritional and functional properties are not well-documented. This study aimed to characterize the physicochemical properties and antioxidant potential of a specific powdered variant of Saraba Keke Manado, produced by a local producer who adheres to traditional formulation methods to ensure authenticity. The study employed a descriptive analytical design. Physicochemical analysis included proximate analysis (moisture, ash, fat, protein, and carbohydrates by difference) and qualitative and quantitative phytochemical screening. Proximate analysis revealed a composition of moisture (2.92%), ash (1.58%), fat (5.42%), protein (7.63%), and a high carbohydrate content (82.45%), likely stemming from the complex spice base and traditional sweeteners used in the recipe. Qualitative screening showed that alkaloids were strongly present (+++), while flavonoids, tannins, saponins, triterpenoids, and phenolics were detected at a lower level (+). Quantitative analysis showed mean concentrations of tannins (2.63 mg/g), flavonoids (12.92 mg/g), and total phenolics (6.23 mg/g). The DPPH assay demonstrated very strong antioxidant activity with an IC50 value of 35.01 ppm, which is explicitly classified as very strong because it is below the 50 ppm threshold. While these findings reflect the profile of the specific sample analyzed, they provide a scientific baseline for future standardization. Saraba Keke Manado possesses a notable nutritional profile rich in bioactive phytochemicals, particularly flavonoids and phenolics, supporting its potential as a functional health beverage.